The study of lexical units denoting household items in comparative and metaphorical domains - Mashhura Abdujalilova (Goodwood Publishing, 2025)
Purpose: This study aims to examine the role of lexical units in advancing lexicography and understanding how languages evolve across different cultural contexts. The research highlights how lexical fields, dictionary theories, and cultural perceptions influence the categorization and interpretation of reality. Methodology: A qualitative literature review was conducted, drawing from studies in lexicography, sociolinguistics, and comparative linguistics. The analysis focused on three main areas: theoretical frameworks used in dictionaries, the organization of lexical fields, and cross-cultural perspectives on language categorization. Results: Findings indicate that lexical units are central to lexicography not only for dictionary compilation but also for documenting linguistic innovation. Researchers emphasize the importance of lexical fields such as household items, kinship terms, and technological vocabulary, which reveal both semantic shifts and cultural adaptation. Cross-cultural studies further demonstrate that the way nations classify and describe reality reflects deeper worldviews and societal values. Conclusion: Lexical studies strengthen the scientific basis of lexicography by connecting linguistic theory with cultural practices, ensuring that dictionaries remain relevant to contemporary users. Limitations: The study is limited to secondary sources, without primary data collection from fieldwork. Future research could incorporate corpus-based analysis or ethnographic approaches for richer insights. Contribution: This research contributes to lexicographic scholarship by underlining the necessity of analyzing lexical units as dynamic cultural markers. It provides a framework for linguists, lexicographers, and language learners to engage with vocabulary as both a linguistic and cultural phenomenon.